“[C]losure is something I may never obtain”: (In)consolation in Yewande Omotoso’s An Unusual Grief (2022) and Onyi Nwabineli’s Someday, Maybe (2022) - Cédric COURTOIS (E-REA)
Both Yewande Omotoso’s An Unusual Grief (2022) and Onyi Nwabineli’s Someday, Maybe (2022) address the shattering effects of grief after the sudden and tragic loss of a loved one to suicide. They tackle “the ugliness” and “the untidiness” of grief and question the possibility of finding any consolation in this context. First, I analyse the stakes behind both diasporic writers’ exploration of the shattering “desolation” that grief represents, by delving into the formal elements that enable them to articulate desolation and trauma. I then explore issues related to repairing, caring and consoling in both novels by taking a look at the tears that are shed and the modalities of this time of and for consolation, before I finally take a look at the metaphor of excavation as the main characters search for meaning and, possibly, comfort, after the aforementioned loss. The issue of the (im)possibility of “closure” will be raised as the characters’ excavating endeavour aims to “unravel the mystery” of these deaths, notably through working and writing through loss and grief.